Radiotherapy Dosing for Locally Advanced Non-Small Cell Lung Carcinoma: “MTD” or “ALARA”? - Ohri, Nitin (Frontiers in Oncology, 2017)
Locally-advanced non-small cell lung cancer (LA-NSCLC) is typically treated with thoracic radiotherapy, often in combination with cytotoxic chemotherapy. Despite tremendous advances in the evaluation, treatment techniques, and supportive care measures provided to LA-NSCLC patients, local disease progression and distant metastases frequently develop following definitive therapy. A recent landmark randomized trial demonstrated that radiotherapy dose escalation may reduce survival rates, highlighting our poor understanding of the effects of thoracic radiotherapy for LA-NSCLC. Here we present rationale for further studies of radiotherapy dose escalation as well as arguments for exploring relatively low radiotherapy doses for LA-NSCLC.